New distributional records of the family Sphecidae (Hymenoptera) in Azerbaijan - M.M. Maharramov (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
Data on 27 species of nine genera of digger wasps of the family Sphecidae collected in Nakhchivan Autonomous Republic of Azerbaijan are presented. Of them, 20 species are recorded for the fauna of Azerbaijan for the first time. This article is based on the material of more than 170 specimens, collected by the authors in July 2018 and June 2019 in 30 localities of the republic. Currently, 258 species of digger wasps (Sphecidae – 27; Crabronidae – 231) are known from this country. It is assumed that the number of sphecid species in Azerbaijan may be at least twice as large.